2008
DOI: 10.1093/imrn/rnn148
|View full text |Cite
|
Sign up to set email alerts
|

Recursion Formulae of Higher Weil-Petersson Volumes

Abstract: In this paper we study effective recursion formulae for computing intersection numbers of mixed ψ and κ classes on moduli spaces of curves. By using the celebrated Witten-Kontsevich theorem, we generalize Mulase-Safnuk form of Mirzakhani's recursion and prove a recursion formula of higher Weil-Petersson volumes. We also present recursion formulae to compute intersection pairings in the tautological rings of moduli spaces of curves.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…Finally, we show that the families of Virasoro algebras used in [23,27,29,30,32,33] for the study of the topological recursion also fit into our framework and have a natural geometrical interpretation (see Section 4.4). In particular, it's shown that a family of τ -functions satisfying KdV and Virasoro is equivalent to a family of actions of the Witt algebra.…”
Section: Arxiv:11100729v2 [Mathag] 7 Jul 2015mentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, we show that the families of Virasoro algebras used in [23,27,29,30,32,33] for the study of the topological recursion also fit into our framework and have a natural geometrical interpretation (see Section 4.4). In particular, it's shown that a family of τ -functions satisfying KdV and Virasoro is equivalent to a family of actions of the Witt algebra.…”
Section: Arxiv:11100729v2 [Mathag] 7 Jul 2015mentioning
confidence: 87%
“…Recent results on intersection theory are based on the so-called topological recursion [23,27,29,30,32,33] which are formulae involving families of τ -functions depending on an infinite number of parameters such that the whole family lies entirely on the space of functions satisfying KdV and Virasoro constraints. One of these families already appeared in Kontsevich's work [25,Section 3.4].…”
Section: Universal Familymentioning
confidence: 99%
“…There exist several methods for computing the integrals (7.1), including application of the Virasoro constraints [43,44,24,46,54,38], the quasi-triviality approach [22,57,28], as well as an interesting method in the original paper of [1]. We propose a yet different approach, based on Thm.…”
Section: Application To Higher Weil-petersson Volumesmentioning
confidence: 99%
“…For generalizations of (III) to the case of intersection numbers involving higher Mumford's κ-classes see [LX1] , [E] and [Ka].…”
Section: Referencesmentioning
confidence: 99%